2007
DOI: 10.1088/0963-0252/17/1/015012
|View full text |Cite
|
Sign up to set email alerts
|

Ion acoustic wave studies near the presheath/sheath boundary in a weakly collisional argon/xenon plasma

Abstract: Ion acoustic wave (IAW) phase velocities are measured near the sheath/presheath boundary in a weakly collisional argon/xenon plasma. Wave profiles versus position are measured using a boxcar averager with a gate width of 30 ns and CW excitation at 50 or 75 kHz. Variable gate delays allow measurement of details of the wave close to the boundary. It is shown that the phase velocity at the presheath/sheath boundary is approximately twice the phase velocity in the bulk plasma for both argon and argon/xenon plasmas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…Since the function κ → ∞ as η se → 0, the scaling analysis of Eq. (11) shows that L sh → 0 in this limit, as confirmed by Fig. 1.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Since the function κ → ∞ as η se → 0, the scaling analysis of Eq. (11) shows that L sh → 0 in this limit, as confirmed by Fig. 1.…”
Section: Discussionsupporting
confidence: 76%
“…[5][6][7][8][9]). Only recently has their detailed experimental investigation become possible [10][11][12]. Sheaths are present in the edge of magnetically confined fusion plasmas, at the interface between spacecrafts and space plasmas, in the fabrication of semiconductor devices, and wherever a plasma interacts with a solid surface.…”
Section: Introductionmentioning
confidence: 99%
“…Langmuir probe biased at À67 V to collect ion saturation current. A Boxcar averager 19 was employed to do time sampling and averaging. A family of spatial profiles of the signal amplitude versus launcher-detector separation were created by systematically incrementing the trigger delay with the result that the phase velocity of the IAWs could be easily measured.…”
Section: Ion Acoustic Wave Diagnostics (Continuous Wave)mentioning
confidence: 99%
“…In experiments by Saxena et al, 6,13 a rarefactive pulse is found to fission into several pulses. Recently Oksuz et al 14 have measured the phase velocity of ion acoustic wave near the presheath and sheath boundaries in a weakly collisional plasma. Okutsu and Nakamura 15 have carried out a numerical and experimental study of the temporal development of weakly nonlinear, broad ion acoustic pulses.…”
Section: Introductionmentioning
confidence: 99%